Teaching English Language in Early Childhood - Jenny Jingga (Journal of Applied Linguistics, 2022)
Learning English is a crucial skill that will enable youngsters to reach their full potential in the future. They can learn English quickly and successfully if they use the appropriate strategies since early childhood. As a result, it is critical that kids learn English that is both practical and beneficial. For youngsters, learning should not be a stressful experience. It should be entertaining as well as stimulating. Reading, listening, and speaking English should become second nature to them as a result of their study. They will learn more and use English language at a higher level as their confidence grows. This paper outlines various resources for EFL teachers to help youngsters learn a foreign language more effectively since they are in their early childhood. These are designed to help them teaching effectively while also providing the excitement and variety that children require. This paper's final section discusses how to ensure that youngsters learn English using easy approaches that will undoubtedly make teachers' jobs more enjoyable and rewarding. Furthermore, it is expected that the teachers would have enough new ideas to be the most inspiring teachers possible. Keywords : Teaching Language, Early Childhood